A Teaching Path for Java Object Oriented Programming - Su Jian; Weng Wenyong; Wang Zebing (Information Technology and Applications, Proceedings, 2009)
A teaching path for Java programming is discussed in this paper. This path is specially designed for students who have already learned C language and begin to learn Java object oriented programming. Along this path, the concepts and principles of object oriented programming will be taught to students step by step. The students can learn the specifications of the Java language as well as the underlying ideas of object oriented programming. The students will gradually break through the obstacles between the procedure oriented programming and the object oriented programming.